2018
DOI: 10.1074/jbc.m117.805093
|View full text |Cite
|
Sign up to set email alerts
|

Elevated sodium chloride drives type I interferon signaling in macrophages and increases antiviral resistance

Abstract: Type I IFN production and signaling in macrophages play critical roles in innate immune responses. High salt ( high concentrations of NaCl) has been proposed to be an important environmental factor that influences immune responses in multiple ways. However, it remains unknown whether high salt regulates type I IFN production and signaling in macrophages. Here, we demonstrated that high salt promoted IFNβ production and its signaling in both human and mouse macrophages, and consequentially primed macrophages fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 33 publications
1
36
0
1
Order By: Relevance
“…Increases in Na + have been demonstrated to help fight against the protozoan parasite Leishmania major (45) and against the bacterial pathogen E. coli (42,50). Recent evidence also suggests that elevation in Na + facilitates antiviral responses against vesicle stomatitis virus (51). In this report, we focused on the impact of this Na + microenvironment on the cessation of osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Increases in Na + have been demonstrated to help fight against the protozoan parasite Leishmania major (45) and against the bacterial pathogen E. coli (42,50). Recent evidence also suggests that elevation in Na + facilitates antiviral responses against vesicle stomatitis virus (51). In this report, we focused on the impact of this Na + microenvironment on the cessation of osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…This phenomenon was consistent with the accumulation of salt found in tumour tissues. Previous studies have found that the p38/MAPK pathway regulates NFAT5 in response to high salt, further mediating cellular protective effects and activation of other signalling pathways including inflammatory responses 6,25,56 . In addition, NFAT5 has been implicated in the pathogenesis of autoimmune diseases, such as RA 27 , autoimmune type 1 diabetes (T1D) 57 and EAE 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, enhanced antimicrobial MΦ activity with high Na + is not restrained to anti-parasitic defenses but is also operative against E. coli [1,14]. Moreover, there is evidence that increased extracellular Na + helps in antigen degradation [15] and fighting viral infections [16,17]. In addition, elevated Na + levels prime malignant cells for apoptosis [18,19] and augment the cytotoxic potential of death receptors in cancer cells [20].…”
Section: Introductionmentioning
confidence: 99%